Analysis of exercise behavior and health promotion behavior according to the Theory of Planned Behavior in Taiwanese older adults - Yang, Chin-Cheng; Sia, Wei-Yeng; Mao, Tso-Yen; Shen, Chih-Chien; Hsiao, Ching-Lin (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The purpose of this study was to analyze exercise behavior and health promotion behavior in Taiwanese older adults who regularly participated in exercise courses in an elderly community care center. This analysis was done according to the Theory of Planned Behavior. A survey was conducted on 100 older adults (more than 65 years old) of Central Taiwan. After eliminating the invalid questionnaires, 87 questionnaires were taken back successfully (valid response rate = 87%). Questionnaire data were analyzed by descriptive analysis, confirmatory factor analysis, and structural equation modeling. It was found that the ability to maintain exercise was the most important factor for engaging in health promotion activities. The participation in health exercise courses in a community care center can help older adults to maintain good physical health and can increase social interaction and participation in the community. Therefore, the community health exercise courses are an effective strategy to maintain the regular exercise behavior of older adults in Taiwan.